Analisis Sentimen Pemilihan Gubernur Jawa Barat Tahun 2018 Dengan Aplikasi Twitter Menggunakan Metode Naïve Bayesian Classification - Yusran Tarihoran; Kevin Jeremy Manurip (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
Elections on West Java Governor 2018 are busy discussed in the real world and cyberspace, especially in social media Twitter. Everyone is free to argue about the candidate of West Java Governor 2018 that raises many opinions, not only positive or neutral opinion, but also negative opinion. Nowadays, social media especially Twitter is one of the place to promote or to campaign effectively and efficiently to increase supporters interest. In this case researchers will conduct research on one of the public figures who run for governor elections West Java. The research method used in this research is the Naïve Bayesian Classifer Classification algorithm. The data used is an Indonesian tweet with the keyword Ridwan Kamil (#RidwanKamil) as much as 1031 data tweet every day starting from January 15, 2018 to April 15, 2018. Results from the classification using the Naïve Bayesian Classifier algorithm obtained 690 number of tweets or 67% all data tweets that support Mr. Ridwan Kamil or are positive especially on the work program that will be done and this provides a probability statistics of 73.13% accuracy level Correctly Classified Instances.